Large herbivore-palm interactions modulate the spatial structure of seedling communities and productivity in Neotropical forests - Villar, Nacho [UNESP]; Rocha-Mendes, Fabiana [UNESP]; Guevara, Roger; Galetti, Mauro [UNESP] (Elsevier, 2022)
Top-down control by large herbivores is a well-known driver of plant diversity structure and productivity. Yet, for forest ecosystems the sign and magnitude of herbivore control across resource gradients is not well understood. We conducted a series of replicated large herbivore exclusion experiments in defaunated and non-defaunated Atlantic forests of Brazil to evaluate the effects of large herbivores on tropical plant communities. We hypothesized that the top-down impact of large herbivores on seedling recruitment, species richness, diversity and productivity would change across a natural gradient in the density of a key plant resource, the palm Euterpe edulis, which is thought to act as a foundation species. We found both positive (agonistic) and negative (antagonistic) spatially-structured effects of large herbivores on plant communities driven by an interaction between large herbivores and palm density on non-defaunated sites, but not on defaunated sites. Indeed, through its interaction with large herbivores, palm trees were able to regulate the spatial structure of seedling communities. In the non-defaunated forest, the negative impact of large herbivores on plant recruitment and species richness decreased substantially as palms became more abundant and canopy cover decreased. Furthermore, large herbivores caused a 185% increase but a 194% decrease in aboveground seedling productivity in areas of high and low palm density, respectively. In contrast, in the defaunated forest we did not find any consistent large herbivore impacts on plant recruitment or species richness across the gradient of palm density, and herbivore activity consistently had negative effects on seedling productivity. Analyses using camera trap data indicate that white-lipped peccaries (Tayassu peccari) played a key role in modulating recruitment and seedling productivity, while tapirs (Tapirus terrestris) contributed significantly to an increase in plant diversity, hence playing a functionally complementary role. Our results demonstrate that a key interaction between large forest-dwelling tropical herbivores and their palm resource results in landscape-scale modulation of plant communities through positive and negative spatially-structured feedbacks, and support the view that palms might act as foundation species in tropical forests. Anthropogenic pressures posed by defaunation and illegal palm harvesting in the Neotropics might lead to the functional loss of this interaction and the collapse of the spatial structure along palm density gradients, with cascading effects on the dynamics and productivity of tropical forests.
Keywords: Consumer-resource dynamics; Disturbance; Frugivory; Seed dispersal; Seed predation; Spatial structure; Trampling